Polycyclic aromatic hydrocarbons (PAHs) in road dust collected from Quang Ninh: Contamination levels and potential sources - Ngoc, Nguyen Thuy; Kim, Truong Thi; Anh, Phan Thi Lan; Anh, Duong Hong; Vi, Phung Thi; Viet, Pham Hung (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 1, 2021)
Twenty road dust samples were collected from Ha Long and Cam Pha cities in Quang Ninh province for analysis of polycyclic aromatic hydrocarbons (PAHs) on the USEPA priority pollutant list. Total concentrations of sixteen PAHs in road dust samples of Ha Long and Cam Pha ranged from 232 - 593 ng/g d.w (average: 399 ng/g d.w) and 297 - 1624 ng/g d.w (average: 780 ng/g d.w), respectively. Proportitions of invididiuals were decreased in the order Phe (21% ± 13%) > Pyr (12% ± 6%) > Nap~Fluth (11% ± 6%) > BbF (10% ± 8%), suggesting the similar composition of analyzed PAHs in road dust at two cities. Based on the common diagnostic ratios for the identification of PAHs emission sources, the Fluth/(Fluth+Pyr) ratio (average: 0.43, range: 0.29-0.60), the BaA/(BaA+Chr) ratio (average: 0.30, range: 0.08-0.38), the IcdP/(IcdP+BghiP) ratio (average: 0.30, range: 0.22-0.46) and the BaP/BghiP ratio (average: 0.47 < 0.9) indicated that emissions from traffic activities may be the important sources of PAHs in Quang Ninh.